The Challenges of Handling Neovascular Glaucoma at Undaan Eye Hospital Surabaya, Indonesia: Poster Presentation - Observational Study - General practitioner - Malika, Rosalia Adriani; Nuradianti, Lydia (Majalah Oftalmologi Indonesia, 2023)
Introduction & Objectives : The management of neovascular glaucoma is challenging because frequently it is incurable with poor visual prognosis. Delay in treatment can lead to sight threatening glaucoma. This study aimed to provide an overview of incidence and management of neovascular glaucoma at Undaan Eye Hospital. Methods : This descriptive epidemiology study comprised 111 eyes of 102 patients. The inclusion criteria were patients diagnosed with NVG who came to Undaan Eye Hospital for 1 year (January 2021 to December 2021). Patients with incomplete medical records were excluded. The patient’s age, gender, risk factors, and treatment were reviewed. Results : There were 102 patients (111 eyes) diagnosed with NVG. The patients were mostly men (53,2%) and the mean age was 54.98 ± 12,4 years. Diabetes Mellitus (DM) was observed in 70 (63,1%) eyes, hypertension in 60 (54,1%) eyes, central retinal vein occlusion (CRVO) in 11 (9,9%) eyes, cholesterol in 7 (6,3%) eyes, and branch retinal vein occlusion (BRVO) in 1 (0,9%) eyes. Mean IOP at the time of diagnosis was 42,8 ± 11,2 mmHg. Anti-VEGF (25,2%), trabeculectomy (59,5%), glaucoma drainage device (17,1%), micropulse transscleral cyclophotocoagulation (5,4%) were done as an option of the treatment. Conclusion : NVG is more common in men. Most patients presenting NVG had DM and hypertension with mean IOP of 42,8 mmHg. Trabeculectomy is the most commonly performed procedure.